Frontiers of ferroptosis research: An analysis from the top 100 most influential articles in the field - Cheng, Kunming; Guo, Qiang; Shen, Zefeng; Yang, Weiguang; Zhou, Yan; Sun, Zaijie; Yao, Xiuhua; Wu, Haiyang (Frontiers in Oncology, 2022)
In recent years, ferroptosis has become a research hotspot in programmed cell death. Since the concept of ferroptosis was proposed, a growing number of articles have been published on this topic. Nevertheless, to our knowledge, these ferroptosis-related publications that have received a great deal of attention have not been quantitatively evaluated. In this study, we analyzed the top 100 most influential articles over the past decade through a bibliometric method to characterize the research status and trends in this field. Web of Science Core Collection was searched to identify relevant studies. After being manually screened, the top 100 most cited studies with original data were identified and analyzed. Bibliometric software including VOSviewer and R-Bibliometrix were used to perform visualization analysis. The citation frequency for the top 100 selected articles ranged from 135 to 3603 (326.6 citations on average). These articles originated from 25 countries/regions, with more than half originating from the United States and China. The most frequently nominated author was Stockwell BR from the Columbia University, and of the top 100 articles, 19 listed his name. Three core journals were Nature, Cell and Proceedings of the National Academy of Sciences of the United States of America. In addition to term of ferroptosis, these terms or phrases including cell death, cancer cell, GPX4, pathway, inhibitor, mechanism, iron, lipid peroxidation, resistance, erastin, sorafenib, P53, reactive oxygen species, necroptosis, apoptosis, glutathione peroxidase, ACSL4, autophagy, and SLC7A11 appeared more frequently in the top 100 articles. Overall, although much progress has been made, the research on ferroptosis is still at an early stage. The current attention in this field mainly focuses on potential regulatory mechanism and pathways including key ferroptosis-related genes/molecules, oxidant and antioxidant system, ferroptosis-inducing agents or nanomedicine for cancer therapy, as well as the role of ferroptosis in non-neoplastic disorders. Meanwhile, combination therapeutic strategies targeting ferroptosis in radiotherapy or immunotherapy also deserve further attention.